Menstruating umbilicus! A rare case report of primary umbilical endometriosis with review of literature - Malik, Renuka; Sharma, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Umbilical endometriosis (UE) represents 0.5% to 1% of all cases of extra genital endometriosis. Primary umbilical endometriosis is the presence of ectopic endometrial tissue located in the umbilicus in absence of previous surgery for either gynecological disorders or cesarean section which is defined as secondary umbilical endometriosis. Secondary UE, which is more common than primary UE and is probably due to the iatrogenic dissemination and implant of endometrial cells during either laparoscopic or open surgical procedures. Mrs. X, presented in OPD with an umbilical nodule since 6 months which grew in size and became painful and bled during periods. Imaging studies were done including MRI. A provisional diagnosis of umbilical endometriosis was made as patient had no history of any prior surgery. Patient had no suggestive history of pelvic endometriosis. Diagnostic laparoscopy was done to rule out concomitant pelvic endometriosis followed by wide local excision and umbilical reconstruction was done. By plastic surgeons. Knowledge of this rare condition and correct management is important to avoid recurrence. Medical treatment is only palliative not definitive in this condition.